Plantar fasciitis in athletes: current state of the problem - A. V. Slivin; S. A. Parastaev (National Electronic Information Consortium (NEICON), 2024)
Objective: to consider, based on the analysis of domestic and foreign sources, the main issues of epidemiology, pathogenesis, diagnosis, and treatment of plantar fasciitis in athletes.Materials and methods: an analysis of data from electronic portals such as PubMed-NCBI, Scopus, Google Scholar, Cochrane Library, and "Scientific Electronic Library eLIBRARY.RU" was conducted by request: "plantar fasciitis sport", "plantar fasciitis in athletes", "plantar fasciitis physical therapy". The review analyzed 103 publications, of which 16 are devoted to the problems of plantar fasciitis in sports; 34 meta-analyses, 39 reviews, 11 randomized clinical trials and 19 other studies based on the principles of good clinical practice were included.Results: the prevalence of plantar fasciitis among athletes was evaluated, ranging from 5.2 to 17.5%. It has been demonstrated that the leading morphological change is the degeneration of connective tissue, which, in combination with repetitive microtrauma, can cause pain. In athletes, plantar fasciitis is often accompanied by various biomechanical disorders and is frequently associated with flat feet. It has been noted that ultrasound and magnetic resonance imaging, which allow for the detection of thickening of the plantar fascia and signs of its degenerative changes, as well as X-ray examination of the feet, are considered as additional diagnostic tools. A wide range of approaches to the treatment of plantar fasciitis has been described: pharmacological methods of intervention, physical and rehabilitation medicine, as well as surgical intervention, which have varying degrees of proven efficacy.Conclusion: since plantar fasciitis in athletes is characterized by a high prevalence and resistance to ongoing therapeutic measures, which is reflected in limited studies, the development of pathogenic justified measures for timely diagnosis and treatment of this condition, primarily focusing on biomechanics, will contribute to the athlete's prompt resumption of full training and competitive activities. Directions for further research on the issue of foot pain occurrence in athletes have been proposed.